Currency crises and institutions - Pattama L. Shimpalee (2018)
This study furthers recent literature on currency crises and institutions. The main objective is to re-evaluate the causes of currency crises by focusing on the role played by a broader array of institutional factors and crisis episodes than have previously been considered while at the same time controlling for economic factors. Our dataset consists of over 30 countries covering 13 institutional factors for the period 1984-2002. Two questions are addressed. They are (1) what mix of institutions may contribute to or set the stage for a currency crisis? and (2) what mix of institutions may affect the depth of currency crises as measured by a decline in output? Our findings reveal that institutional as well as economic factors affect the probability of currency crises and that worse institutions are associated with bigger contractions in output during the crisis. In general, our strongest results regarding institutions show that corruption, a de facto fixed exchange rate regime, weak government stability, and weak law and order increase the probability of a currency crisis. We find mixed evidence that deposit insurance, the removal of capital controls, a lack of central bank independence, financial liberalization, and civil law increase the chance of crisis. We find a similar set of factors worsens the contraction in output during a crisis except for deposit insurance, which we find moderates the contraction in output. © 2005 Elsevier Ltd. All rights reserved.